Up-regulation of Glutamate in Painful Human Supraspinatus Tendon Tears. - Franklin, S; Dean, B; Wheway, K; Watkins, B; Javaid, M; Carr, A (SAGE Publications, 2014)
BACKGROUND: Pain related to rotator cuff tendinopathy is a common problem, but little is known regarding the origin and cause of pain from the tendon substance. No study to date has looked at the association between tissue changes and patient outcomes. PURPOSE: To describe the peripheral neuronal phenotype in painful rotator cuff tears and to determine correlations between tissue changes and clinical outcome measures. STUDY DESIGN: Controlled laboratory study. METHODS: Tissue samples of the supraspinatus were taken from patients undergoing surgery to repair a rotator cuff tendon tear. Patients were classified as having small/medium or large/massive tears. Control tissue was obtained from patients undergoing surgery for posttraumatic shoulder instability. Immunohistochemical techniques were performed using antibodies to known nociceptive and neuronal markers as well as general tissue structural markers. RESULTS: There was no correlation between tissue changes and patient-reported outcomes. A significant increase in the expression of glutamate was seen in tendon tears. There were differences in the expression of metabotropic and ionotropic glutamate receptors. Expression changes were also observed for markers of the sensory and autonomic systems; however, no differences were found in neurotrophins. CONCLUSION: Glutamate and the glutaminergic system play a key role in painful human tendon tears; however, the exact role is still uncertain, as glutamate is highly involved in both pain and metabolic pathways. CLINICAL RELEVANCE: This study has identified a number of markers that could be potential therapeutic targets.